Exploring the Islamic Investment Paradigm of Generation Z Muslims on Madura Island Using a Grounded Theory Approach - Nurul Fazirah; Abdur Rohman (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study explores the Islamic investment paradigm among Muslim Generation Z on Madura Island using a Grounded Theory approach. The purpose of this study is to reveal how young Muslims develop their understanding and practice of Islamic finance amid the influences of religiosity, local culture, and economic digitalization. Data were obtained through in-depth interviews with 20 Muslim Gen Z participants selected using purposive and theoretical sampling techniques. Analysis was conducted through the stages of open coding, axial coding, and selective coding based on the Strauss and Corbin model. The results of the study reveal three main paradigms in the interpretation of Islamic investment: (1) the Initial Paradigm, which emphasizes moral compliance and religious authority; (2) the Adaptive Paradigm, which demonstrates the integration of Islamic values and modern economic rationality; and (3) the Innovative Paradigm, which reflects the creative application of sharia principles for sustainability and social welfare. These three paradigms converge in the core concept of Constructive Adaptive Literacy, which describes the dynamic process of Gen Z Muslims in interpreting, adapting, and innovating Islamic financial values according to the social and digital context. Theoretically, this research enriches the study of Sharia financial literacy rooted in cultural religiosity, while practically providing direction for the development of Islamic financial education relevant to the younger generation.